Automatic system for blood donors control with seropositive results in epidemiological tests. - Ariel Menéndez Barrios; Darian Álvarez Rodríguez; Pedro Sánchez Frenes; Enrique Castillo Monzón; Nancy Piloto; Yenixey Lòpez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Background: Prevention of infectious diseases transmission through blood transfusion is one of the biggest challenges in the transfusion field of medicine. Objective: to design a computerized system for blood donors control with seropositive results in epidemiological tests. Methods: A system designed by the Provincial Blood Bank using Microsoft Access as a data base system and DELFHI 7 as associated language. It runs under Windows 2000 or any other superior system with 64 RAM and do not need special requirements of software or hardware. It includes the following data: Full name, age, sex, race, Id number, home address, number of the clinical record in the blood bank, date when the trial took place in each patient, kind of disease diagnosed, technical data of the trial such as: fluorescence, sectional level of the 1st trial as well as the repetition, name of the technician who performed it. Results: It permits to consult general data of donors as well as the disease diagnosed. It also permits to elaborate reports of these patients from any PC of the blood bank acceding with the security password of the program. Conclusions: It constitutes a beneficial tool which permits to improve the notification system established in the program of the web about sexually transmitted diseases from the Minister of Public Health in Cuba.